NENYA: Cascade Reinforcement Learning for Cost-Aware Failure Mitigation at Microsoft 365 - Wang, Lu; Zhao, Pu; Du, Chao; Luo, Chuan; Su, Mengna; Yang, Fangkai; Liu, Yudong; 林庆维, Qingwei Lin; Wang, Min; Dang, Yingnong; Zhang, Hongyu; Rajmohan, Saravan; et al. (SIGKDD 2022, 2022)
Large-scale distributed systems, such as Microsoft 365's database system, require timely mitigation solutions to address failures and improve service availability and reliability. Still, mitigation actions can be costly as they may cause temporal performance degradation and even incur monetary expenses. Mitigation actions can be either administrated in a reactive fashion to contain detected failures or a proactive fashion to reduce potential failures. The proactive mitigation approach typically relies on a two-stage strategy: the prediction model will firstly identify instances (such as databases or disks) with high failure risk, then appropriate mitigation actions chosen by engineers or an automatic bandit learning model can be applied. As information is not fully shared across those two stages, important factors such as mitigation costs and states of instances are often ignored in one of those two stages. To address these issues, we propose NENYA, an end-to-end mitigation solution for a large-scale database system powered by a novel cascade reinforcement learning model. By taking the states of databases as input, NENYA directly outputs mitigation actions and is optimized based on jointly cumulative feedback on mitigation costs and failure rates. As the overwhelming majority of databases do not require mitigation actions, NENYA utilizes a novel cascade decision structure to firstly reliably filter out such databases and then focus on choosing appropriate mitigation actions for the rest. Extensive offline and online experiments have shown that our methods can outperform existing practices in reducing both failure rates of databases and mitigation costs. NENYA has been integrated into Microsoft 365, a productive platform, with sounding success.